Systemic Inflammation Response Index Is a Predictor of Poor Survival in Locally Advanced Nasopharyngeal Carcinoma: A Propensity Score Matching Study - Feng, Yuhua; Zhang, Na; Wang, Sisi; Zou, Wen; He, Yan; Ma, Jin-an; Liu, Ping; Liu, Xianling; Hu, Chunhong; Hou, Tao (Frontiers in Oncology, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is a common malignant cancer in China, and the prognosis factors are rare. In this study, the prognostic values of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune inflammation index (SII) and systemic inflammation response index (SIRI) were assessed in locally-advanced NPC patients. Methods: Patients admitted between January 2012 and December 2015, who received curative radiation or chemoradiation therapy at the Second Xiangya Hospital were retrospectively reviewed, and a total of 516 patients were enrolled. After propensity score matching (PSM), 417 patients were enrolled eventually. The laboratory data and clinical data were collected from the patient’s record. ROC analysis was used to determine the optimal cut-off. Survival curves were analyzed by Kaplan-Meier method. Cox proportional hazard model was used to find out prognostic variables. Results: After PSM, the basic characteristics between patients in the two groups were balanced except for gender (p=0.001), and clinical stage (p=0.036). Univariate analysis showed that NLR (p=0.001), PLR (p=0.008), SII (p=0.001) and SIRI (p＜0.001) were prognostic factors for PFS and OS. However, further multivariate Cox regression analysis showed that only SIRI was an independent predictor of PFS and OS with hazard ratio (HR) at 2.83 (95%CI 1.561-5.131, p=0.001), 5.19 (95%CI 2.588-10.406, p＜0.001), respectively. Conclusion: Our findings indicate that SIRI might be a promising predictive indicator for locally-advanced NPC patients.